Boosting the Synthesis of Pharmaceutically Active Abietane Diterpenes in S. sclarea Hairy Roots by Engineering the GGPPS and CPPS Genes - Vaccaro, Maria Carmela; Alfieri, Mariaevelina; De Tommasi, Nunziatina; Moses, Tessa; Goossens, Alain; Leone, Antonietta (Frontiers in Plant Science, 2020)
Abietane diterpenoids, synthesized in the roots of different Salvia species, such as aethiopinone, 1-oxoaethiopinone, salvipisone and ferruginol, have a variety of known biological activities. We have shown that aethiopinone has promising cytotoxic activity against several human tumor cell lines, including the breast adenocarcinoma MCF7, HeLa, epithelial carcinoma, prostate adenocarcinoma PC3 and human melanoma A375. The low content of these compounds in natural sources, and the limited possibility to synthesize them chemically at low cost, prompted us to optimize the production of abietane diterpenoids by targeting genes of the methylerythritol phosphate (MEP) pathway, from which they are derived. Here, we report our current and ongoing efforts to boost the metabolic flux towards this interesting class of compounds in Salvia sclarea hairy roots (HRs). By silencing the gene encoding the ent-copalyl-diphosphate synthase gene (entCPPS), acting at the lateral geranylgeranyl pyrophosphate (GGPP) competitive gibberellin route, enhanced the content of ADs in S. sclarea HRs, indicating also indirectly that the GGPP pool is a metabolic constraint to the accumulation of abietane diterpenes. This was confirmed by overxpressing the GGPPS gene (geranyl-geranyl disphosphate synthase) which triggered also a significant 8-fold increase of abietane diterpene content above the basal constitutive level, with a major boosting effect on aethiopinone accumulation in S. sclarea HRs. A significant accumulation of aethiopinone and other AD compounds was also achieved by overexpressing the CPPS gene (copalyl disphosphate synthase) pointing to this biosynthetic step as another potential metabolic target for optimizing the biosynthesis of this class of compounds. However, by co-expressing of GGPPS and CPPS genes, albeit significant, the increase of abietane diterpenoids was less effective than that obtained by overexpressing the two genes individually. Taken together, the results presented here add novel and instrumental knowledge to a rational design of a hairy root-based platform to yield reliable amounts of ADs for a deeper understanding of their molecular pharmacological targets and potential future commercialization